1996
DOI: 10.1046/j.1365-2265.1996.727548.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific stimulation of brain serotonin mediated neurotransmission by dexfenfluramine does not restore growth hormone responsiveness in obese women

Abstract: This study confirms that GH secretion in response to stimuli with varying mechanisms of action is blunted in obese subjects. A decrease of central serotonin mediated neurotransmission does not appear to play a role in the pathogenesis of this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…However, the GH response to GHRH is increased in the presence of dexfenfluramine in patients with android obesity and in those with a reduction of insulin levels (although this latter response may have been influenced by dietary habits) (64). Other authors have not observed any increrase in the GH response to GHRH in obese women under treatment with dexfenfluramine (63).…”
Section: Pharmacological Agents Modulating Energetic Homeostasismentioning
confidence: 92%
See 1 more Smart Citation
“…However, the GH response to GHRH is increased in the presence of dexfenfluramine in patients with android obesity and in those with a reduction of insulin levels (although this latter response may have been influenced by dietary habits) (64). Other authors have not observed any increrase in the GH response to GHRH in obese women under treatment with dexfenfluramine (63).…”
Section: Pharmacological Agents Modulating Energetic Homeostasismentioning
confidence: 92%
“…In addition, the increase of adrenocorticotrophin (ACTH) and cortisol after naloxone administration (in both obese and non‐obese women) was attenuated through a 7‐d treatment with dexfenfluramine (61). ACTH and cortisol response to adrenocorticotrophin releasing hormone (CRH) were not affected by treatment with dexfenfluramine (63). However, the GH response to GHRH is increased in the presence of dexfenfluramine in patients with android obesity and in those with a reduction of insulin levels (although this latter response may have been influenced by dietary habits) (64).…”
Section: Pharmacological Agents Modulating Energetic Homeostasismentioning
confidence: 99%
“…The same agent did not affect ACTH and cortisol responses to CRH (58); however, GH response to GHRH was shown to be increased in patients with android obesity, concomitantly with reduction in insulin levels (although the latter may be influenced by dietary habits) (46). Other authors have not detected increase in GH response to GHRH in obese women treated with dexfenfluramine (47).…”
Section: Endocrine and Metabolic Effectsmentioning
confidence: 98%
“…Entretanto, a resposta de GH ao GHRH é aumentada com dexfenfluramina em pacientes com obesidade andróide e os níveis de insulina foram reduzidos (embora esta última resposta possa ter sido influenciada pela dieta) (59). Outros autores não observaram aumento da resposta de GH ao GHRH em mulheres obesas submetidas a tratamento com dexfenfluramina (60). O mazindol leva à redução da insulina e do GH durante teste oral de tolerância à glicose e promove elevação de T 4 , embora não altere FSH, LH, testosterona, renina, angiotensina II, taxa metabólica basal, reflexo aquileu e 17-cetosteróides (61).…”
Section: Farmacocinética Clínicaunclassified